Lyon-University Hospital Experience with Gemtuzumab Ozogamicin Therapy in Acute Myeloid Leukemia: a ‘Real-Life’ Study - Laurino, Marica (Mediterr J Hematol Infect Dis, 2020)
Ninety-four adults with newly diagnosed or relapsed/refractory acute myeloid leukemia (AML) were treated with fractionated doses of gemtuzumab ozogamicin (GO) at one-single French center over ten years. We attempted to define predictive factors for response and survival. The overall response rate was 70% (86% in newly diagnosed and 65% in relapsed/refractory AML). Mortality during induction was 6%. Disease-free survival (DFS) and overall survival at three years after GO treatment was 36% and 31%, respectively. Median DFS in relapsed/refractory patients was eight months with a 3-year DFS at 34%. Among remitters, allogeneic hematopoietic stem cell transplantation (HSCT) can be performed in 28 cases (42%), including two patients in first-line therapy and 26 in further line. In relapsed/refractory patients undergoing allogeneic HSCT after responding to GO therapy, the median DFS was not reached. Incidences of transplant-related mortality, grade ≥ 3 acute graft-versus-host (GvH) disease, and extensive chronic GvH disease were 11%, 14%, and 25%, respectively. No sinusoidal obstruction syndromes were reported among allografted patients as among the other patients in the studied cohort. GO-based chemotherapy is a viable option for the treatment of relapsed/refractory AML patients and is a feasible schedule as a bridge to allogeneic transplant.